Our actions are our future - a zero hunger world by 2030 is possible - Rahman, Habibar; Kennady, Vijayalakshmy (2018)
Hunger, a major component which is threatening the World for past so many years. Still, the prevalence of hunger is increasing day by day globally. Various innovative steps and research activities have to be taken into consideration so that the fact of achieving Zero Hunger World will be possible by 2030. The major factor behind the arousal of hunger is poverty. The people below poverty line in developing countries are the most affected. Most of the people are small scale livestock farmers who are mainly dependent on their daily production for their livelihood. Main focus of hunger challenge should be towards the small scale livestock farmers, so that their daily production strategy in enhancing their daily income. This in turn helps to eradicate poverty and global hunger in achieving a Zero Hunger World by 2030.